INTEGRATION OF SATELLITE AND TERRESTRIAL COMMUNICATION NETWORKS IN THE CONTEXT OF GLOBAL INTERNET ACCESS (American Journal of Technology and Applied Sciences, 2024)
This article examines the current state of standardization, architectural integration models, and key technical challenges, including spectrum management, high latency variability, and inter-segment roaming. Implementation recommendations and practical scenarios are provided, demonstrating the importance of hybrid networks for universal connectivity.